Cost-effectiveness and incidence of renewable energy promotion in Germany - Christoph Böhringer; Florian Landis; Miguel Angel Tovar Rea\~nos (University of Oldenburg, Department of Economics, 2016)
Over the last decade Germany has boosted renewable energy in power production by means of massive subsidies. The flip side are very high electricity prices which raises concerns that the transition cost towards a renewable energy system will be mainly borne by poor households. In this paper, we combine computable general equilibrium and microsimulation analysis to investigate the cost-effectiveness and incidence of Germany's renewable energy promotion. We find that the regressive effects of renewable energy promotion could be attenuated by alternative subsidy financing mechanisms which achieve the same level of electricity generation from renewable energy sources.
Keywords: Q42; H23; C63; 330; Renewable energy policy; feed-in tariffs; CGE; microsimulation